1995
DOI: 10.3168/jds.s0022-0302(95)76667-x
|View full text |Cite
|
Sign up to set email alerts
|

Additives Containing Bacteria and Enzymes for Alfalfa Silage

Abstract: First-cutting alfalfa was wilted, harvested from alternate rows, left untreated or treated with additives containing lactic acid bacteria and enzymes (cellulase, amylase, and pectinase), and ensiled in bag silos. Inoculation increased lactic acid bacteria from 5 x 10(4) to 1 x 10(6) cfu/g of forage. Because treatments were bagged consecutively, the DM of treated silages was higher than that of untreated silage. However, after 4 d of ensiling, the pH of treated silage, about 4.3, was lower than that of untreate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
1
5

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 12 publications
7
29
1
5
Order By: Relevance
“…This reasoning is in line with the observation that the addition of cellulase significantly increased lactate concentrations with a concomitant decrease in pH. Thus, it can be suggested that the addition of cellulase effectively provided more substrate for fermentation by the LAB (Stokes, 1992;Ridla and Uchida, 1993;Sheperd et al, 1995). Furthermore, the addition of LAB instead of cellulase significantly increased the lactic acid content, suggesting that the numbers of epiphytic LAB in OPF may limit the conversion of sugars into lactate to attain a pH <4.5.…”
Section: Fermentation Qualitysupporting
confidence: 74%
See 1 more Smart Citation
“…This reasoning is in line with the observation that the addition of cellulase significantly increased lactate concentrations with a concomitant decrease in pH. Thus, it can be suggested that the addition of cellulase effectively provided more substrate for fermentation by the LAB (Stokes, 1992;Ridla and Uchida, 1993;Sheperd et al, 1995). Furthermore, the addition of LAB instead of cellulase significantly increased the lactic acid content, suggesting that the numbers of epiphytic LAB in OPF may limit the conversion of sugars into lactate to attain a pH <4.5.…”
Section: Fermentation Qualitysupporting
confidence: 74%
“…This result is corroborated by Ridla and Uchida (1993) who also showed that the addition of cellulase decreases the content of cell wall carbohydrates associated with the NDF and ADF content. It appears that the additional cellulase stimulated the conversion of cellulose to WSC thereby rendering glucose available for LAB and potential subsequent conversion to lactate (Stokes, 1992;Ridla and Uchida, 1993;Sheperd et al, 1995). The effective degradation of NDF and ADF by cellulase is also reflected by the improvement of DM digestibility.…”
Section: Chemical Composition and Digestibilitymentioning
confidence: 86%
“…A utilização conjunta de lactobacilos e enzimas (celulase, hemicelulase, pectinase etc.) têm apresentado resultados controvertidos; alguns autores citam efeitos positivos nos parâmetros fermentativos (WOOLFORD, 1984;SHEPERD et al, 1995) e outros indicam a possibilidade de ações antagônicas (STOKES, 1992). Outros trabalhos têm constatado pouco efeito de inoculantes microbianos e aditivos enzimáticos sobre a eficiência da fermentação de silagens de alfafa (WHITE et al 1990), sugerindo que a inoculação com bactérias formadoras de ácido lático somente seria efetiva quando suplementada com carboidratos solúveis ou ainda com aumento dos níveis de MS (VALINOTTI e PICHARD, 1993).…”
Section: Introductionunclassified
“…Lactobacillus buchneri). Homofermentative LAB inoculants enhance the rate of acidification and reduce the final pH or protein breakdown in silages (Sheperd et al 1995;Weinberg and Muck 1996;Driehuis et al 1997;Aksu et al 2004). However, homofermentative LAB could induce aerobic deterioration of whole-crop cereal silages due to insufficient production of volatile fatty acids (VFA) to inhibit fungi (Weinberg et al 1993;Filya et al 2000).…”
Section: Introductionmentioning
confidence: 99%